Causes of project delay and cost overrun of mega projects in peninsular Malaysia - Nur Aliya Najiha, Tamrin (2019)
Project delay and cost overrun are two most commonly issues happen which tend to cause troubles in any construction project, especially the mega construction project. These two issues are generally regarded as the most problematic, complex, and risky issues encountered in a mega construction project. Many studies in Malaysia and also from the other countries point out that the issue of project delay and cost overrun are most commonly happen in developing countries includes Malaysia. Therefore, the identification or establishment of the causes that will lead to project delay and cost overrun in megaprojects is necessary and vital in order to put an effort in avoiding or overcoming this problem. This is corresponds to the main objective of this study which is to study the causes of the project delay and cost overruns in megaprojects in Peninsular Malaysia. The data acquired from the survey used a Likert Scale and analysed using Relative Important Index (RII).The study found that the three highest ranking for the causes of project delay of megaprojects by overall respondents are mistakes during construction by contractors, delay in progress payment and financial difficulties. While the causes of cost overrun for megaprojects declaring the three highest ranking is from the aspect of site management which are schedule delay, inaccurate time and cost estimated and inadequate monitoring and controlling.